REASSESSING TABOO: RESHAPING THE PERCEPTION AND REORIENTING THE APPROACH - Darin Rifda Malya Haq (PARADIGM: Journal of Language and Literary Studies, 2025)
This paper examines how Shaila Abdullah’s Saffron Dreams (2009) and Laila Lalami’s Hope and Other Dangerous Pursuits (2005) portray actions commonly labelled as taboo and invite readers to move beyond immediate moral judgment. Focusing on Arissa Illahi’s decision to remove her hijab and Faten Khatibi’s decision to enter sex work, the study argues that these actions should be read in relation to the social, religious, emotional, and material pressures that shape them. Using qualitative close textual analysis, the paper applies the frameworks of Muslimah narratives, Islamic feminism, and resistance to examine the protagonists’ conditions before, during, and after their decisions. The analysis shows that both novels situate transgressive acts within contexts of Islamophobia, migration, economic vulnerability, gendered expectation, and social exclusion. As a result, Arissa’s and Faten’s choices emerge not as simple violations of religious or social norms, but as complex forms of negotiation, survival, and constrained agency. The findings suggest that Abdullah and Lalami use narrative empathy to challenge reductive perceptions of Muslim women and to reveal the human complexity behind stigmatized actions. Ultimately, this paper demonstrates that both novels encourage a more patient and humane approach to interpreting taboo choices.